The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/978-3-030-63549-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Coronavirus Disease 2019

Abstract: There are profound sex differences in coronavirus disease 2019 (COVID-19) outcomes, with higher morbidity and mortality in males compared to females. The possible mechanisms implicated in this sex bias include the direct effects of sex hormones on the innate and adaptive immune systems, as well as the differential activity of immune-related genes in sex chromosomes. These male-female differences in COVID-19 outcomes highlight the need for sex-disaggregated data to elaborate effective public health policies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…Moreover, biological differences in the immune systems of men and women exist, and they may affect the capacity to fight COVID-19 infection. Men appear to be at a greater risk with COVID-19 compared to women, whose higher immunologic response is probably associated with decreased mortality ( Chiarella, Pabelick, & Prakash, 2021 ). Furthermore, certain differences in cardiac manifestations in COVID-19 must be considered as a core component ( Sharma, Volgman, & Michos, 2020 ).…”
Section: Related Work: Identifying Causal Explaining Factors On Sex/g...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, biological differences in the immune systems of men and women exist, and they may affect the capacity to fight COVID-19 infection. Men appear to be at a greater risk with COVID-19 compared to women, whose higher immunologic response is probably associated with decreased mortality ( Chiarella, Pabelick, & Prakash, 2021 ). Furthermore, certain differences in cardiac manifestations in COVID-19 must be considered as a core component ( Sharma, Volgman, & Michos, 2020 ).…”
Section: Related Work: Identifying Causal Explaining Factors On Sex/g...mentioning
confidence: 99%
“…A confounder is a variable with incoming arrows in the graph to both sensitive attribute and an outcome (a cause for both) and creates spurious non causal relationship between the two. Variable and source Class Group Comments Hormones ( Chiarella et al, 2021 , Dana et al, 2020 , Klein et al, 2020 , Peckham et al, 2020 , Traish and Morgentaler, 2021 ) Mediator Sex-related Bio Var Male hormone testosterone is associated with increased vulnerability, whereas female hormones are believed to play a protecting role. Immune response ( Chiarella et al, 2021 , Dana et al, 2020 , Grzelak et al, 2020 ) Mediator Sex-related Bio Var More protective antibodies are formed in women and they last longer.…”
Section: Confounders and Mediators Between Sex And Covid-19 Vulnerabi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the beginning of the pandemic, in several countries there was the need to collect sex-disaggregated data in order to evaluate the incidence, the mortality rate and the disease treatment according to the sex. Importantly, demographic and clinical data collected globally demonstrated that the rate of COVID-19, including asymptomatic and mild forms, is similar between the sexes [11]. Instead, in our data, which include only patients hospitalized and who had attended emergency room, the percentage of females was lower than that of males both in the first and the second wave.…”
Section: Relationship With Previous Studiesmentioning
confidence: 55%
“…There is a significant sex bias in the immune response to viral infections. This bias is considered the result of male-female differences in sex chromosomes and sex hormone milieu [11]. In general, female immune system responds to pathogens more efficiently, producing higher amounts of interferon (INF) and antibodies.…”
Section: Significance and Interpretation Of Study Findingsmentioning
confidence: 99%